PERENCANAAN TANGKI RESERVOIR DISTRIBUSI AIR BERSIH PADA PERUSAHAAN AIR MINUM (PAM) KAPASITAS 57000 LITER (STUDI KASUS DESA LABURUNCI KEC. PASAR WAJO KAB. BUTON) - Anto, Herbianto; Salimin, Salimin; Sudia, Budiman (Teknik Mesin Universitas Halu Oleo, 2017)
This study aims to planning reservoir tank distribusion water clean to PAM Laburunci Village. This study,researcher uses Microsoft Excel, Microsoft Word, Auto Cad, Geobasis Google Earth, Sketchup, initial data,the previous study and and guiding books. This planning the pressure of tank is obtained 0,005 kg/mm2,permissible voltage of 2.11 kg/mm2, the thickness of Shell plate is 8 mm, 10 mm off bottom plate, 7 mm ofroof plate. The voltage of circumferensial is 1.18 kg/mm2, the logitudinal voltage of 0.53 kg/mm2. The lengthof curvature of 595 mm/600 mm, a large of force roll 1298.88 kg, the strength of plate roll 20.09 kg/mm2. Thewelding type of welding electrodes SMAW E7018 in conection of blunt intersection welded and welding ofcorner conuace surface. The welding be done of bundle welded earlier with the length 60 mm and thedistance between bunde weldeol of 200 mm. Thr Estimatig useful age is acquired more than 30 years. Theprojection result of Laburunci’s village society for the next 10 years in the year 3744 society in 2027, thewater needs in Laburunci’s vilage for the next 10 years = 384600 liters/day. The tank of capacity plans57000 liters. It is completed by the water pump in Laburunci’s of capacity of 25 m3/hour if it is done seventimes a recharging in a day need 17 hours 16 minutes have reached 399000 liters. The water volume 399000liters/day can fulfill the water need Laburunci’s vilage society in the next 10 years namely 384600liter’s/day.Keywords: Planning tank, the value of the parameters and lifespan.